2015
DOI: 10.3390/rs70911954
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Response to a Typhoon-Induced Flood with an SAR-Derived Map of Inundated Areas: Case Study and Validation

Abstract: Abstract:We report the successful case of a rapid response to a flash flood in I-Lan County of Taiwan with a map of inundated areas derived from COSMO-SkyMed 1 radar satellite imagery within 24 hours. The flood was caused by the intensive precipitation brought by Typhoon Soulik in July 2013. Based on the ensemble forecasts of trajectory, an urgent request of spaceborne SAR imagery was made 24 hours before Typhoon Soulik made landfall. Two COSMO-SkyMed images were successfully acquired when the center of Typhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
0
19
0
2
Order By: Relevance
“…It passed over the warm waters of the Kuroshio Current the following day and later made landfall on 12 July 2013 in northern Taiwan with torrential rains of 900 mm (35 in) in Bailan, destructive winds of 190 km/h (120 mph), and gusts as high as 220 km/h (140 mph). As a result, the low-lying areas of Ilan City were seriously flooded [61], and a significant amount of terrestrial materials were flushed from the watersheds of mountainous areas through the Lanyang River to the Lanyang River plume. Since this is one of the major agriculture areas of Taiwan, a lot of fertilizer with ingredients such as nitrogen and phosphorous was also exported to the coast off northeastern Taiwan.…”
Section: Influence Of Typhoonsmentioning
confidence: 99%
“…It passed over the warm waters of the Kuroshio Current the following day and later made landfall on 12 July 2013 in northern Taiwan with torrential rains of 900 mm (35 in) in Bailan, destructive winds of 190 km/h (120 mph), and gusts as high as 220 km/h (140 mph). As a result, the low-lying areas of Ilan City were seriously flooded [61], and a significant amount of terrestrial materials were flushed from the watersheds of mountainous areas through the Lanyang River to the Lanyang River plume. Since this is one of the major agriculture areas of Taiwan, a lot of fertilizer with ingredients such as nitrogen and phosphorous was also exported to the coast off northeastern Taiwan.…”
Section: Influence Of Typhoonsmentioning
confidence: 99%
“…However, the limitations of deploying a UAV under severe weather conditions to cover a large area were also highlighted by this mission. To remove those limitations, we were motivated to seek another type of imagery from SAR to derive an inundation map [4]. Chung et al reported a successful case of rapid response with a map of inundated areas derived from COSMO-SkyMed 1 radar satellite imagery during the July 2013 flood in I-Lan County in Taiwan, which was caused by Typhoon Soulik [4].…”
Section: Synthetic Aperture Radar Imagerymentioning
confidence: 99%
“…In the aftermath of Japan's earthquake and tsunami on March 11, 2011, we demonstrated that Formosat-2 imagery can be rapidly acquired, processed, and distributed through the Internet to global users by deploying the system through cloud servers [3]. Therefore, FPERS was developed with an intention to collect and display the huge amount of relevant geospatial imagery, including Formosat-2 pre-and post-flood imagery (2-m resolution) used to detect and monitor barrier lakes, the synthetic aperture radar (SAR) imagery used to derive an inundation map [4], and the high-spatial-resolution photos taken by unmanned aerial vehicles (UAV) to evaluate the damage to river channels and structures due to a debris flow [5]. In spite of these successes, these data were mainly used for disaster assessment at the post-flood stage.…”
Section: Introductionmentioning
confidence: 99%
“…This will contribute to generating flood extent maps and estimating the flood depth. Moreover, the flood maps from the proposed method can be used for the cross-validation of those from the existing methods (Chung et al, 2015;Twele et al, 2016;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%